Immunotherapy in Non-Small Cell Lung Cancer With Actionable Mutations Other Than EGFR - Karan Seegobin; Umair Majeed; Nathaniel Wiest; Rami Manochakian; Yanyan Lou; Yujie Zhao (Frontiers in Oncology, 2021)
While first line targeted therapies are the current standard of care treatment for non-small cell lung cancer (NSCLC) with actionable mutations, the cancer cells inevitably acquire resistance to these agents over time. Immune check-point inhibitors (ICIs) have improved the outcomes of metastatic NSCLC, however, its efficacy in those with targetable drivers is largely unknown. In this manuscript, we reviewed the published data on ICI therapies in NSCLC with ALK, ROS1, BRAF, c-MET, RET, NTRK, KRAS, and HER2 (ERBB2) alterations. We found that the objective response rates (ORRs) associated with ICI treatments in lung cancers harboring the BRAF (0–54%), c-MET (12–49%), and KRAS (18.7-66.7%) alterations were comparable to non-mutant NSCLC, whereas the ORRs in RET fusion NSCLC (less than10% in all studies but one) and ALK fusion NSCLC (0%) were relatively low. The ORRs reported in small numbers of patients and studies of ROS1 fusion, NTRK fusion, and HER 2 mutant NSCLC were 0–17%, 50% and 7–23%, respectively, making the efficacy of ICIs in these groups of patients less clear. In most studies, no significant correlation between treatment outcome and PD-L1 expression or tumor mutation burden (TMB) was identified, and how to select patients with NSCLC harboring actionable mutations who will likely benefit from ICI treatment remains unknown.